Plant community type and small‐scale disturbances, but not altitude, influence the invasibility in subarctic ecosystems. Issue 3 (3rd December 2012) - Milbau, Ann; Shevtsova, Anna; Osler, Nora; Mooshammer, Maria; Graae, Bente J.
Summary: Little of our knowledge about invasibility comes from arctic and alpine ecosystems, despite increasing plant migration and invasion in those regions. Here, we examine how community type, altitude, and small‐scale disturbances affect invasibility in a subarctic ecosystem. Over a period of 4 yr, we studied seedling emergence and establishment in 17 species sown in gaps or undisturbed vegetation in four subarctic community types ( Salix scrub, meadow, rich heath, poor heath) along an elevation gradient. Invasibility was lowest in rich heath and highest in Salix scrub. Small disturbances significantly increased the invasibility in most communities, thereby showing the importance of biotic resistance to invasion in subarctic regions. Unexpectedly, invasibility did not decrease with increasing elevation, and it was also not related to summer temperature. Our data suggest that biotic resistance might be more important than abiotic stress for invasibility in subarctic tundra and that low temperatures do not necessarily limit seedling establishment at high altitudes. High elevations are therefore potentially more vulnerable to invasion than was originally thought. Changes in community composition as a result of species migration or invasion are most likely to occur in Salix scrub and meadow, whereas Empetrum ‐dominated rich heath will largely remain unchanged.